A release film for metal lithium belt calendering and a preparation method thereof

CN122898016APending Publication Date: 2026-10-13GUANGDONG RUIHUA NEW MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611093949.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-22
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

[0002]金属锂带质地柔软,屈服强度低,与轧辊易发生粘附,在压延过程中易出现褶皱、撕裂等缺陷,现有技术大多采用三明治夹膜压延工艺,将金属锂带夹持在双层离型膜之间送入轧辊,解决锂带粘辊、断带的问题

Benefits of technology

本发明中,聚氨酯丙烯酸酯的分子链上含有有机硅、氨基甲酸酯键和丙烯酸酯双键,有机硅作为软段赋予抗静电涂料较低的表面张力,氨基甲酸酯结构赋予涂料在PET膜表面良好的附着力;支化结构能够限制涂料体系的微相分离,丙烯酸酯双键具有光敏性,紫外固化交联密度高,在剥离时无胶残留,功能化碳纳米管具有较好的导电性,且导电性不依赖环境湿度,在高温下性质稳定,不易析出;解决了涂层附着力不足、抗静电性能易失效的问题。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure REF-OBJ-1784690300893-000001
    Figure REF-OBJ-1784690300893-000001
Patent Text Reader

Abstract

The application discloses a release film for metal lithium belt calendering and a preparation method thereof, and relates to the technical field of release films.In the application, polyurethane acrylate containing organic silicon, urethane bonds and acrylate double bonds and functionalized carbon nanotubes containing double bonds are prepared as components of antistatic coating.Under the action of a photoinitiator, the double bonds are copolymerized to form an antistatic coating, the organic silicon serves as a soft segment to endow the antistatic coating with relatively low surface tension, the urethane structure endows the coating with good adhesion on the surface of a PET film, the branched structure can limit the microphase separation of the coating system, the acrylate double bonds have photosensitivity, ultraviolet curing crosslinking density is high, no glue is left during peeling, the functionalized carbon nanotubes have good conductivity, the conductivity is not dependent on environmental humidity, the properties are stable at high temperatures, and the functionalized carbon nanotubes are not easy to precipitate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of release film technology, specifically a release film for rolling lithium metal strips and its preparation method. Background Technology

[0002] Lithium metal strips are soft and have low yield strength, making them prone to adhesion to rolls. During the calendering process, defects such as wrinkles and tears are likely to occur. Most existing technologies use a sandwich calendering process to sandwich the lithium metal strip between two layers of release film before feeding it into the rolls, thus solving the problems of lithium strip sticking to the rolls and strip breakage.

[0003] Lithium-ion film calendering requires high surface energy, low release force, and good antistatic properties. Commercially available release films tend to lose their antistatic properties after prolonged use, making them unsuitable for application. To improve antistatic performance, conductive polymers are typically added to the coating, but insufficient coating adhesion remains a problem.

[0004] Therefore, this invention proposes a release film for rolling lithium metal strips and its preparation method, and develops a release film with long-lasting antistatic properties and good stability, so that the lithium metal strips can obtain better ductility during the rolling process. Summary of the Invention

[0005] The purpose of this invention is to provide a release film for rolling lithium metal strips and its preparation method, in order to solve the problems raised in the prior art.

[0006] To achieve the above objectives, the present invention provides the following technical solution: a method for preparing a release film for rolling lithium metal strips, comprising the following processes: Take a PET film, coat its upper and lower surfaces with an antistatic coating, and then cure it with ultraviolet light to form an antistatic coating, thus obtaining a release film.

[0007] Furthermore, the PET film undergoes corona treatment under the following conditions: power 5.0~6.0kW, voltage 7.0~8.0kV, and treatment time 5~10s.

[0008] Furthermore, the antistatic coating has a thickness of 22~32μm on both the upper and lower surfaces.

[0009] Furthermore, the UV curing process conditions are: irradiation energy 2500~3000mJ / cm². 2 The irradiation time is 25-35 seconds, and the irradiation distance is 18-25 cm.

[0010] Furthermore, the antistatic coating comprises the following components by weight: 80-100 parts polyurethane acrylate, 10-20 parts functionalized carbon nanotubes, 12-20 parts diluent, 0.5-1.5 parts photoinitiator, and 20-40 parts solvent.

[0011] Furthermore, the diluent is 1,6-hexanediol diacrylate; The photoinitiator is photoinitiator 184; The solvent is ethyl acetate.

[0012] Furthermore, the preparation process of the polyurethane acrylate is as follows: Step 1: Under an inert atmosphere, polyhydroxy organosilicon, isophorone diisocyanate and dibutyltin dilaurate are mixed and heated to react. Then, 1,4-butanediol and ethyl acetate are added and the reaction is maintained at a certain temperature to obtain the terminal isocyanate prepolymer. Step 2: Mix the terminal isocyanate prepolymer, pentaerythritol triacrylate, p-hydroxyanisole and ethyl acetate, and heat to react to obtain polyurethane acrylate.

[0013] Furthermore, in step 1, the mass ratio of polyhydroxy organosilicon, isophorone diisocyanate, dibutyltin dilaurate, 1,4-butanediol and ethyl acetate is 100:(70~75):(0.10~0.18):(3~4):140.

[0014] Furthermore, in step 1, the process conditions for the heating reaction are: temperature 75~82℃, time 0.6~1.0h; In step 1, the process conditions for the heat preservation reaction are: temperature 75~82℃, time 3.0~3.5h.

[0015] Furthermore, in step 2, the mass ratio of the terminal isocyanate prepolymer, pentaerythritol triacrylate, p-hydroxyanisole, and ethyl acetate is 100:(60~70):(0.10~0.15):130.

[0016] Furthermore, in step 2, the process conditions for the heating reaction are: temperature 68~72℃, time 4~6h.

[0017] In the above technical solution, firstly, the hydroxyl groups of polyhydroxy organosilicon react with the isocyanate groups of isophorone diisocyanate to generate urethane bonds, and 1,4-butanediol is used as a chain extender to generate terminal isocyanate prepolymers; then, the hydroxyl groups of pentaerythritol triacrylate react with the terminal isocyanate prepolymers to introduce double bonds, thereby obtaining polyurethane acrylates.

[0018] Furthermore, the polyhydroxy organosilicon is prepared by the following process: S1: Diethylenetriamine, allyl glycidyl ether and anhydrous methanol are mixed and heated under nitrogen atmosphere. After the reaction is completed, the mixture is distilled to obtain a polyhydroxy double bond compound. S2: Under nitrogen atmosphere protection, terminal hydrogen silicone oil and toluene are mixed and heated to 45~55℃. Then, a catalyst is added and stirred for 40~60 min. Then, a polyhydroxy double bond compound is added within 1 h, and the temperature is increased to react. After the reaction is completed, the mixture is distilled and dried under vacuum to obtain polyhydroxy organosilicon.

[0019] Furthermore, in S1, the ratio of diethylenetriamine, allyl glycidyl ether, and anhydrous methanol is (2.6~3.0) g : (7.0~8.0) g : 12 mL.

[0020] Furthermore, in S1, the process conditions for the heating reaction are: temperature 55~60℃, time 10~12h; In S1, the distillation process conditions are: temperature 40~45℃, time 1.5~2.0h.

[0021] Furthermore, in S2, the ratio of terminal hydrogen silicone oil, toluene, and polyhydroxy double bond compound is (2~4) mL: 50 mL: (3~5) mL; In S2, the amount of catalyst added is 0.4~0.6% of the mass of the terminal hydrogen silicone oil; The catalyst is a chloroplatinic acid isopropanol solution, wherein the mass fraction of chloroplatinic acid is 30%.

[0022] Furthermore, in S2, the process conditions for the heating reaction are: temperature 65~75℃, time 2~4h; In S2, the distillation process conditions are: temperature 70~78℃, time 1.8~2.2h; In S2, the vacuum drying process conditions are: temperature 50~60℃, time 0.8~1.0h.

[0023] In the above technical solution, firstly, the primary amino group of diethylenetriamine reacts with the epoxy group of allyl glycidyl ether to generate hydroxyl and secondary amino groups, thus obtaining a polyhydroxy double bond compound; then, the double bond is used to perform hydrosilylation with the hydrogen-silicon bond of the terminal hydrogen silicone oil, retaining the hydroxyl group, to obtain a polyhydroxy organosilicon.

[0024] Furthermore, the preparation process of the functionalized carbon nanotubes is as follows: Under a nitrogen atmosphere, carboxylated carbon nanotubes, polyhydroxy double bond compounds, tetrabutylammonium bromide and N,N-dimethylformamide were mixed, ultrasonically dispersed, and heated to react. After the reaction was completed, the mixture was filtered, washed and dried to obtain functionalized carbon nanotubes.

[0025] Furthermore, the ratio of carboxylated carbon nanotubes, polyhydroxy double bond compounds, tetrabutylammonium bromide and N,N-dimethylformamide is (0.8~1.2) g : (3.0~4.0) g : (0.15~1.0) g : 150 mL.

[0026] Furthermore, the ultrasonic dispersion process conditions are: frequency 20~40kHz, time 60~90min; The process conditions for the heating reaction are: temperature 100~120℃, time 12~16h; The drying process conditions are: temperature 50~60℃, time 10~12h.

[0027] Furthermore, the carboxylated carbon nanotubes and polyhydroxy double bond compounds are vacuum dried at 50-60°C for 10-12 hours before use.

[0028] In the above technical solution, the surface carboxyl groups of carboxylated carbon nanotubes are esterified with the hydroxyl groups of polyhydroxy double bond compounds to introduce double bonds and obtain functionalized carbon nanotubes. The surface double bonds can prevent carbon nanotubes from agglomerating and can also form crosslinks with polyurethane acrylate during the curing process, giving the antistatic coating stable antistatic properties.

[0029] Compared with the prior art, the beneficial effects of the present invention are: In this invention, the molecular chain of polyurethane acrylate contains organosilicon, urethane bonds, and acrylate double bonds. Organosilicon, as a soft segment, imparts low surface tension to the antistatic coating, while the urethane structure provides good adhesion to the PET film surface. The branched structure can restrict microphase separation in the coating system, the acrylate double bonds are photosensitive, and the UV curing crosslinking density is high, leaving no adhesive residue upon peeling. The functionalized carbon nanotubes have good conductivity, which is independent of environmental humidity, and are stable at high temperatures, making them less prone to precipitation. This invention solves the problems of insufficient coating adhesion and easy failure of antistatic properties. Detailed Implementation

[0030] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0031] In the following examples, the relevant raw materials are: PET film with a thickness of 100 μm; diluent: 1,6-hexanediol diacrylate; photoinitiator: photoinitiator 184; solvent: ethyl acetate; terminal hydrogen silicone oil with a hydrogen content of 1.2~1.5%; catalyst: isopropanol solution of chloroplatinic acid, wherein the mass fraction of chloroplatinic acid is 30%; carboxylated carbon nanotubes with a diameter of 10~20 nm, a length of 10~30 μm, and an electrical conductivity >150 S / cm; and polypropylene glycol with a molecular weight of 400.

[0032] Example 1: A method for preparing a release film for rolling lithium metal strips, comprising the following processes: (1) Preparation of functionalized carbon nanotubes: Carboxylated carbon nanotubes and polyhydroxy double bond compounds were vacuum dried at 60 °C for 12 h. Under nitrogen atmosphere protection, the vacuum-dried carboxylated carbon nanotubes, polyhydroxy double bond compounds, tetrabutylammonium bromide and N,N-dimethylformamide were mixed at a ratio of 1.2 g: 4.0 g: 1.0 g: 150 mL, ultrasonically dispersed at 40 kHz for 90 min, heated to 120 °C and reacted for 16 h. After the reaction was completed, the mixture was filtered, washed and dried at 60 °C for 12 h to obtain functionalized carbon nanotubes. (2) Preparation of polyhydroxy organosilicon: S1: Diethylenetriamine, allyl glycidyl ether and anhydrous methanol were mixed at a ratio of 3.0 g: 8.0 g: 12 mL and heated to 60 °C for 12 h under a nitrogen atmosphere. After the reaction was completed, the mixture was distilled at 45 °C for 2.0 h to obtain a polyhydroxy double bond compound. S2: Under a nitrogen atmosphere, terminal hydrogen silicone oil and toluene were mixed and heated to 55°C. Then, a catalyst was added and stirred for 60 min. A polyhydroxy double bond compound was then added over 1 h, and the mixture was heated to 75°C and reacted for 4 h. After the reaction was complete, the mixture was distilled at 78°C for 2.2 h and then vacuum dried at 60°C for 1.0 h to obtain a polyhydroxy organosilicon. The ratio of terminal hydrogen silicone oil, toluene, and polyhydroxy double bond compound was 4 mL: 50 mL: 5 mL. The amount of catalyst added was 0.6% of the mass of the terminal hydrogen silicone oil. (3) Preparation of polyurethane acrylate: Step 1: Under an inert atmosphere, polyhydroxy organosilicon, isophorone diisocyanate, and dibutyltin dilaurate were mixed and heated to 82°C for 1.0 h. Then, 1,4-butanediol and ethyl acetate were added, and the reaction was maintained at 82°C for 3.5 h to obtain the terminal isocyanate prepolymer. The mass ratio of polyhydroxy organosilicon, isophorone diisocyanate, dibutyltin dilaurate, 1,4-butanediol, and ethyl acetate was 100:75:0.18:4:140. Step 2: Mix the terminal isocyanate prepolymer, pentaerythritol triacrylate, p-hydroxyanisole and ethyl acetate in a mass ratio of 100:70:0.15:130, heat to 72°C and react for 6 hours to obtain polyurethane acrylate; (4) Preparation of release film: A PET film was first subjected to corona treatment, then an antistatic coating was applied to its upper and lower surfaces, followed by UV curing to form an antistatic coating and obtain a release film. The corona treatment process conditions were: power 6.0kW, voltage 8.0kV, and treatment time 10s; the antistatic coating thickness on both the upper and lower surfaces was 32μm; the UV curing process conditions were: irradiation energy 3000mJ / cm². 2 The irradiation time is 35 seconds and the irradiation distance is 25 cm. The antistatic coating consists of the following components by mass: 100 parts polyurethane acrylate, 20 parts functionalized carbon nanotubes, 20 parts diluent, 1.5 parts photoinitiator, and 40 parts solvent.

[0033] Example 2: A method for preparing a release film for rolling lithium metal strips, comprising the following processes: (1) Preparation of functionalized carbon nanotubes: Carboxylated carbon nanotubes and polyhydroxy double bond compounds were vacuum dried at 55 °C for 11 h. Under nitrogen atmosphere protection, the vacuum-dried carboxylated carbon nanotubes, polyhydroxy double bond compounds, tetrabutylammonium bromide and N,N-dimethylformamide were mixed at a ratio of 1.0 g: 3.5 g: 0.50 g: 150 mL, ultrasonically dispersed at 30 kHz for 75 min, heated to 110 °C and reacted for 14 h. After the reaction was completed, the mixture was filtered, washed and dried at 55 °C for 11 h to obtain functionalized carbon nanotubes. (2) Preparation of polyhydroxy organosilicon: S1: Diethylenetriamine, allyl glycidyl ether and anhydrous methanol were mixed at a ratio of 2.8 g: 7.5 g: 12 mL and heated to 58 °C for 11 h under a nitrogen atmosphere. After the reaction was completed, the mixture was distilled at 43 °C for 1.8 h to obtain a polyhydroxy double bond compound. S2: Under a nitrogen atmosphere, terminal hydrogen silicone oil and toluene were mixed and heated to 50°C. Then, a catalyst was added and stirred for 50 min. A polyhydroxy double bond compound was then added over 1 h, and the mixture was heated to 70°C and reacted for 3 h. After the reaction was complete, the mixture was distilled at 75°C for 2.0 h and then vacuum dried at 55°C for 0.9 h to obtain a polyhydroxy organosilicon. The ratio of terminal hydrogen silicone oil, toluene, and polyhydroxy double bond compound was 3 mL: 50 mL: 4 mL. The amount of catalyst added was 0.5% of the mass of the terminal hydrogen silicone oil. (3) Preparation of polyurethane acrylate: Step 1: Under an inert atmosphere, polyhydroxy organosilicon, isophorone diisocyanate, and dibutyltin dilaurate were mixed and heated to 80°C for 0.8 h. Then, 1,4-butanediol and ethyl acetate were added, and the reaction was maintained at 80°C for 3.3 h to obtain the terminal isocyanate prepolymer. The mass ratio of polyhydroxy organosilicon, isophorone diisocyanate, dibutyltin dilaurate, 1,4-butanediol, and ethyl acetate was 100:73:0.15:3.5:140. Step 2: Mix the terminal isocyanate prepolymer, pentaerythritol triacrylate, p-hydroxyanisole and ethyl acetate in a mass ratio of 100:65:0.13:130, heat to 70°C and react for 5 hours to obtain polyurethane acrylate; (4) Preparation of release film: A PET film was first subjected to corona treatment, then an antistatic coating was applied to its upper and lower surfaces, followed by UV curing to form an antistatic coating and obtain a release film. The corona treatment process conditions were: power 5.5kW, voltage 7.5kV, and treatment time 8s; the antistatic coating thickness on both the upper and lower surfaces was 28μm; the UV curing process conditions were: irradiation energy 2800mJ / cm². 2 The irradiation time was 30 seconds, and the irradiation distance was 22 cm. The antistatic coating consists of the following components by mass: 90 parts polyurethane acrylate, 11 parts functionalized carbon nanotubes, 16 parts diluent, 1.0 part photoinitiator, and 30 parts solvent.

[0034] Example 3: A method for preparing a release film for rolling lithium metal strips, comprising the following processes: (1) Preparation of functionalized carbon nanotubes: Carboxylated carbon nanotubes and polyhydroxy double bond compounds were vacuum dried at 50 °C for 10 h. Under nitrogen atmosphere protection, the vacuum-dried carboxylated carbon nanotubes, polyhydroxy double bond compounds, tetrabutylammonium bromide and N,N-dimethylformamide were mixed at a ratio of 0.8 g: 3.0 g: 0.15 g: 150 mL, ultrasonically dispersed at 20 kHz for 60 min, heated to 100 °C and reacted for 12 h. After the reaction was completed, the mixture was filtered, washed and dried at 50 °C for 10 h to obtain functionalized carbon nanotubes. (2) Preparation of polyhydroxy organosilicon: S1: Diethylenetriamine, allyl glycidyl ether and anhydrous methanol were mixed at a ratio of 2.6 g: 7.0 g: 12 mL and heated to 55 °C for 10 h under a nitrogen atmosphere. After the reaction was completed, the mixture was distilled at 40 °C for 1.5 h to obtain a polyhydroxy double bond compound. S2: Under a nitrogen atmosphere, terminal hydrogen silicone oil and toluene were mixed and heated to 45°C. Then, a catalyst was added and stirred for 40 min. A polyhydroxy double bond compound was then added over 1 h, and the mixture was heated to 65°C and reacted for 2 h. After the reaction was complete, the mixture was distilled at 70°C for 1.8 h and then vacuum dried at 50°C for 0.8 h to obtain a polyhydroxy organosilicon. The ratio of terminal hydrogen silicone oil, toluene, and polyhydroxy double bond compound was 2 mL: 50 mL: 3 mL. The amount of catalyst added was 0.4% of the mass of the terminal hydrogen silicone oil. (3) Preparation of polyurethane acrylate: Step 1: Under an inert atmosphere, polyhydroxy organosilicon, isophorone diisocyanate, and dibutyltin dilaurate were mixed and heated to 75°C for 0.6 h. Then, 1,4-butanediol and ethyl acetate were added, and the reaction was maintained at 75°C for 3.0 h to obtain the terminal isocyanate prepolymer. The mass ratio of polyhydroxy organosilicon, isophorone diisocyanate, dibutyltin dilaurate, 1,4-butanediol, and ethyl acetate was 100:70:0.10:3:140. Step 2: Mix the terminal isocyanate prepolymer, pentaerythritol triacrylate, p-hydroxyanisole and ethyl acetate in a mass ratio of 100:60:0.10:130, heat to 68°C and react for 4 hours to obtain polyurethane acrylate; (4) Preparation of release film: A PET film was first subjected to corona treatment, then an antistatic coating was applied to its upper and lower surfaces, followed by UV curing to form an antistatic coating and obtain a release film. The corona treatment process conditions were: power 5.0kW, voltage 7.0kV, and treatment time 5s; the antistatic coating thickness on both the upper and lower surfaces was 22μm; the UV curing process conditions were: irradiation energy 2500mJ / cm². 2 The irradiation time was 25 seconds, and the irradiation distance was 18 cm. The antistatic coating consists of the following components by mass: 80 parts polyurethane acrylate, 10 parts functionalized carbon nanotubes, 12 parts diluent, 0.5 parts photoinitiator, and 20 parts solvent.

[0035] Comparative Example 1: Compared with Example 1, the functionalized carbon nanotubes were replaced with carbon nanotubes, while all other conditions remained unchanged, as follows: (1) Preparation of polyhydroxy organosilicon: S1: Diethylenetriamine, allyl glycidyl ether and anhydrous methanol were mixed at a ratio of 3.0 g: 8.0 g: 12 mL and heated to 60 °C for 12 h under a nitrogen atmosphere. After the reaction was completed, the mixture was distilled at 45 °C for 2.0 h to obtain a polyhydroxy double bond compound. S2: Under a nitrogen atmosphere, terminal hydrogen silicone oil and toluene were mixed and heated to 55°C. Then, a catalyst was added and stirred for 60 min. A polyhydroxy double bond compound was then added over 1 h, and the mixture was heated to 75°C and reacted for 4 h. After the reaction was complete, the mixture was distilled at 78°C for 2.2 h and then vacuum dried at 60°C for 1.0 h to obtain a polyhydroxy organosilicon. The ratio of terminal hydrogen silicone oil, toluene, and polyhydroxy double bond compound was 4 mL: 50 mL: 5 mL. The amount of catalyst added was 0.6% of the mass of the terminal hydrogen silicone oil. (2) Preparation of polyurethane acrylate: Step 1: Under an inert atmosphere, polyhydroxy organosilicon, isophorone diisocyanate, and dibutyltin dilaurate were mixed and heated to 82°C for 1.0 h. Then, 1,4-butanediol and ethyl acetate were added, and the reaction was maintained at 82°C for 3.5 h to obtain the terminal isocyanate prepolymer. The mass ratio of polyhydroxy organosilicon, isophorone diisocyanate, dibutyltin dilaurate, 1,4-butanediol, and ethyl acetate was 100:75:0.18:4:140. Step 2: Mix the terminal isocyanate prepolymer, pentaerythritol triacrylate, p-hydroxyanisole and ethyl acetate in a mass ratio of 100:70:0.15:130, heat to 72°C and react for 6 hours to obtain polyurethane acrylate; (3) Preparation of release film: A PET film was first subjected to corona treatment, then an antistatic coating was applied to its upper and lower surfaces, followed by UV curing to form an antistatic coating and obtain a release film. The corona treatment process conditions were: power 6.0kW, voltage 8.0kV, and treatment time 10s; the antistatic coating thickness on both the upper and lower surfaces was 32μm; the UV curing process conditions were: irradiation energy 3000mJ / cm². 2 The irradiation time is 35 seconds and the irradiation distance is 25 cm. The antistatic coating consists of the following components by mass: 100 parts polyurethane acrylate, 20 parts carbon nanotubes, 20 parts diluent, 1.5 parts photoinitiator, and 40 parts solvent.

[0036] Comparative Example 2: Compared with Example 1, the polyhydroxy organosilicon was replaced with polypropylene glycol, while the other conditions remained unchanged, as follows: (1) Preparation of functionalized carbon nanotubes: Carboxylated carbon nanotubes and polyhydroxy double bond compounds were vacuum dried at 60 °C for 12 h. Under nitrogen atmosphere protection, the vacuum-dried carboxylated carbon nanotubes, polyhydroxy double bond compounds, tetrabutylammonium bromide and N,N-dimethylformamide were mixed at a ratio of 1.2 g: 4.0 g: 1.0 g: 150 mL, ultrasonically dispersed at 40 kHz for 90 min, heated to 120 °C and reacted for 16 h. After the reaction was completed, the mixture was filtered, washed and dried at 60 °C for 12 h to obtain functionalized carbon nanotubes. (2) Preparation of polyurethane acrylate: Step 1: Under an inert atmosphere, polypropylene glycol, isophorone diisocyanate, and dibutyltin dilaurate were mixed and heated to 82°C for 1.0 h. Then, 1,4-butanediol and ethyl acetate were added, and the reaction was maintained at 82°C for 3.5 h to obtain the terminal isocyanate prepolymer. The mass ratio of polypropylene glycol, isophorone diisocyanate, dibutyltin dilaurate, 1,4-butanediol, and ethyl acetate was 100:75:0.18:4:140. Step 2: Mix the terminal isocyanate prepolymer, pentaerythritol triacrylate, p-hydroxyanisole and ethyl acetate in a mass ratio of 100:70:0.15:130, heat to 72°C and react for 6 hours to obtain polyurethane acrylate; (4) Preparation of release film: A PET film was first subjected to corona treatment, then an antistatic coating was applied to its upper and lower surfaces, followed by UV curing to form an antistatic coating and obtain a release film. The corona treatment process conditions were: power 6.0kW, voltage 8.0kV, and treatment time 10s; the antistatic coating thickness on both the upper and lower surfaces was 32μm; the UV curing process conditions were: irradiation energy 3000mJ / cm². 2 The irradiation time is 35 seconds and the irradiation distance is 25 cm. The antistatic coating consists of the following components by mass: 100 parts polyurethane acrylate, 20 parts functionalized carbon nanotubes, 20 parts diluent, 1.5 parts photoinitiator, and 40 parts solvent.

[0037] Comparative Example 3: Compared with Example 1, no functionalized carbon nanotubes were added to the antistatic coating, and all other conditions remained unchanged, as follows: (1) Preparation of polyhydroxy organosilicon: S1: Diethylenetriamine, allyl glycidyl ether and anhydrous methanol were mixed at a ratio of 3.0 g: 8.0 g: 12 mL and heated to 60 °C for 12 h under a nitrogen atmosphere. After the reaction was completed, the mixture was distilled at 45 °C for 2.0 h to obtain a polyhydroxy double bond compound. S2: Under a nitrogen atmosphere, terminal hydrogen silicone oil and toluene were mixed and heated to 55°C. Then, a catalyst was added and stirred for 60 min. A polyhydroxy double bond compound was then added over 1 h, and the mixture was heated to 75°C and reacted for 4 h. After the reaction was complete, the mixture was distilled at 78°C for 2.2 h and then vacuum dried at 60°C for 1.0 h to obtain a polyhydroxy organosilicon. The ratio of terminal hydrogen silicone oil, toluene, and polyhydroxy double bond compound was 4 mL: 50 mL: 5 mL. The amount of catalyst added was 0.6% of the mass of the terminal hydrogen silicone oil. (2) Preparation of polyurethane acrylate: Step 1: Under an inert atmosphere, polyhydroxy organosilicon, isophorone diisocyanate, and dibutyltin dilaurate were mixed and heated to 82°C for 1.0 h. Then, 1,4-butanediol and ethyl acetate were added, and the reaction was maintained at 82°C for 3.5 h to obtain the terminal isocyanate prepolymer. The mass ratio of polyhydroxy organosilicon, isophorone diisocyanate, dibutyltin dilaurate, 1,4-butanediol, and ethyl acetate was 100:75:0.18:4:140. Step 2: Mix the terminal isocyanate prepolymer, pentaerythritol triacrylate, p-hydroxyanisole and ethyl acetate in a mass ratio of 100:70:0.15:130, heat to 72°C and react for 6 hours to obtain polyurethane acrylate; (3) Preparation of release film: A PET film was first subjected to corona treatment, then an antistatic coating was applied to its upper and lower surfaces, followed by UV curing to form an antistatic coating and obtain a release film. The corona treatment process conditions were: power 6.0kW, voltage 8.0kV, and treatment time 10s; the antistatic coating thickness on both the upper and lower surfaces was 32μm; the UV curing process conditions were: irradiation energy 3000mJ / cm². 2 The irradiation time is 35 seconds and the irradiation distance is 25 cm. The antistatic coating consists of the following components by mass: 100 parts polyurethane acrylate, 20 parts diluent, 1.5 parts photoinitiator, and 40 parts solvent.

[0038] Comparative Example 4: Compared with Example 1, no functionalized carbon nanotubes were added to the antistatic coating, and polyhydroxy silicone was replaced with polypropylene glycol, while other conditions remained unchanged, as follows: (1) Preparation of polyurethane acrylate: Step 1: Under an inert atmosphere, polypropylene glycol, isophorone diisocyanate, and dibutyltin dilaurate were mixed and heated to 82°C for 1.0 h. Then, 1,4-butanediol and ethyl acetate were added, and the reaction was maintained at 82°C for 3.5 h to obtain the terminal isocyanate prepolymer. The mass ratio of polypropylene glycol, isophorone diisocyanate, dibutyltin dilaurate, 1,4-butanediol, and ethyl acetate was 100:75:0.18:4:140. Step 2: Mix the terminal isocyanate prepolymer, pentaerythritol triacrylate, p-hydroxyanisole and ethyl acetate in a mass ratio of 100:70:0.15:130, heat to 72°C and react for 6 hours to obtain polyurethane acrylate; (2) Preparation of release film: A PET film was first subjected to corona treatment, then an antistatic coating was applied to its upper and lower surfaces, followed by UV curing to form an antistatic coating and obtain a release film. The corona treatment process conditions were: power 6.0kW, voltage 8.0kV, and treatment time 10s; the antistatic coating thickness on both the upper and lower surfaces was 32μm; the UV curing process conditions were: irradiation energy 3000mJ / cm². 2 The irradiation time is 35 seconds and the irradiation distance is 25 cm. The antistatic coating consists of the following components by mass: 100 parts polyurethane acrylate, 20 parts diluent, 1.5 parts photoinitiator, and 40 parts solvent.

[0039] Experimental testing: The release films obtained in the examples and comparative examples were made into 20×10cm samples, and their various performances were tested: Antistatic stability test: Referring to ASTM D257, the surface resistance value of the sample was tested using a surface resistance meter to characterize its antistatic performance; then the sample was placed in a constant temperature chamber at 50±2℃ and 80% relative humidity for 48h. After the sample was removed, the surface resistance value was measured again to characterize its antistatic performance stability under high temperature and high humidity environment. Residual adhesion rate: First, test the initial adhesion value of the sample and record it as A. Then, after the TESA7475 tape is bonded to the release film for 24 hours, peel it off and measure the adhesion value after peeling, which is recorded as B. Residual adhesion rate = B / A × 100%; Release force test: TESA7475 tape is bonded to the release film, and after 24 hours, it is peeled off at 180° and 300 mm / min. The peel force is recorded and the average value is taken as the release force. The experimental data are shown in Table 1 below.

[0040]

[0041] Based on the data in the table above, the following conclusions can be drawn: Compared with Example 1, Comparative Example 1 replaced functionalized carbon nanotubes with carbon nanotubes. The initial resistance and the resistance value of the resulting release film were improved to a certain extent, while the residual adhesion rate did not change much. This is because the unfunctionalized carbon nanotubes have uneven distribution and agglomeration, which have a certain impact on conductivity. Compared with Example 1, Comparative Example 2 replaced polyhydroxy organosilicon with polypropylene glycol. The initial resistance value did not change much, but the resistance value increased significantly after being placed in a high temperature and high humidity environment. The residual adhesion rate decreased significantly. This is because organosilicon, as a soft segment, gives the antistatic coating a lower surface tension and a certain high temperature resistance. The branched structure can limit the microphase separation of the coating system and improve the adhesion of the antistatic coating to a certain extent. Compared with Example 1, Comparative Example 3 did not add functionalized carbon nanotubes to the antistatic coating, and the resistance value increased significantly while the residual adhesion rate did not change much. This is because the coating does not contain conductive components, and the resulting release film does not have antistatic properties. Compared with Example 1, Comparative Example 4 did not add functionalized carbon nanotubes to the antistatic coating, and replaced polyhydroxy silicone with polypropylene glycol, resulting in a significant increase in resistance and a more obvious decrease in residual adhesion. In Examples 1-3, the release force was relatively stable. In Comparative Examples 1-4, the release force decreased and fluctuated significantly, indicating instability. In summary, the antistatic coating components in this application can improve the antistatic performance and residual adhesion of the release film, solving the problems of insufficient coating adhesion and easy failure of antistatic performance; and the release force is moderate, ensuring stable adhesion of the release film and easy removal without leaving any residue.

[0042] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the invention can be implemented in other specific forms without departing from the spirit or essential characteristics of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description. Thus, it is intended that all variations falling within the meaning and scope of equivalents of the claims be included within the present invention.

Claims

1. A method for preparing a release film for rolling lithium metal strips, characterized in that: Including the following processes: Take a PET film, coat its upper and lower surfaces with an antistatic coating, and cure it with ultraviolet light to form an antistatic coating, thus obtaining a release film; The antistatic coating comprises the following components by weight: 80-100 parts polyurethane acrylate, 10-20 parts functionalized carbon nanotubes, 12-20 parts diluent, 0.5-1.5 parts photoinitiator, and 20-40 parts solvent.

2. The method for preparing a release film for rolling lithium metal strips according to claim 1, characterized in that: The preparation process of the polyurethane acrylate is as follows: Step 1: Under an inert atmosphere, polyhydroxy organosilicon, isophorone diisocyanate and dibutyltin dilaurate are mixed and heated to react. Then, 1,4-butanediol and ethyl acetate are added and the reaction is maintained at a certain temperature to obtain the terminal isocyanate prepolymer. Step 2: Mix the terminal isocyanate prepolymer, pentaerythritol triacrylate, p-hydroxyanisole and ethyl acetate, and heat to react to obtain polyurethane acrylate.

3. The method for preparing a release film for rolling lithium metal strips according to claim 2, characterized in that: The polyhydroxy organosilicon is prepared by the following process: S1: Diethylenetriamine, allyl glycidyl ether and anhydrous methanol are mixed and heated under nitrogen atmosphere to obtain a polyhydroxy double bond compound. S2: Under nitrogen atmosphere protection, terminal hydrogen silicone oil and toluene are mixed and heated to 45~55℃. Then, a catalyst is added and stirred for 40~60 min. Then, a polyhydroxy double bond compound is added within 1 h and the temperature is increased to react, thus obtaining polyhydroxy organosilicon.

4. The method for preparing a release film for rolling lithium metal strips according to claim 1, characterized in that: The preparation process of the functionalized carbon nanotubes is as follows: Under a nitrogen atmosphere, carboxylated carbon nanotubes, polyhydroxy double bond compounds, tetrabutylammonium bromide, and N,N-dimethylformamide were mixed, ultrasonically dispersed, and heated to react, yielding functionalized carbon nanotubes.

5. The method for preparing a release film for rolling lithium metal strips according to claim 2, characterized in that: In step 1, the mass ratio of polyhydroxy organosilicon, isophorone diisocyanate, dibutyltin dilaurate, 1,4-butanediol and ethyl acetate is 100:(70~75):(0.10~0.18):(3~4):

140.

6. The method for preparing a release film for rolling lithium metal strips according to claim 2, characterized in that: In step 2, the mass ratio of terminal isocyanate prepolymer, pentaerythritol triacrylate, p-hydroxyanisole and ethyl acetate is 100:(60~70):(0.10~0.15):

130.

7. The method for preparing a release film for rolling lithium metal strips according to claim 3, characterized in that: In S1, the ratio of diethylenetriamine, allyl glycidyl ether, and anhydrous methanol is (2.6~3.0) g : (7.0~8.0) g : 12 mL.

8. The method for preparing a release film for rolling lithium metal strips according to claim 3, characterized in that: In S2, the ratio of terminal hydrogen silicone oil, toluene, and polyhydroxy double bond compound is (2~4) mL: 50 mL: (3~5) mL.

9. The method for preparing a release film for rolling lithium metal strips according to claim 4, characterized in that: The ratio of carboxylated carbon nanotubes, polyhydroxy double bond compounds, tetrabutylammonium bromide and N,N-dimethylformamide is (0.8~1.2) g : (3.0~4.0) g : (0.15~1.0) g : 150 mL.

10. The release film for rolling lithium metal strips prepared by the method according to any one of claims 1 to 9.